Advancing fish diversity monitor in degraded marine ecosystem with environmental DNA approach: Unveiling hidden riches - Peiwen Jiang; Youwei Xu; Shuai Zhang; Shannan Xu; Yancong Cai; Yutao Yang; Zuozhi Chen; Min Li (Ecological Indicators, 2024)
Comprehending fish diversity through multiple dimensions is a crucial aspect in advancing our understanding of fish populations and promoting sustainable fisheries as well as diversity conservation. Traditional research on fish diversity has been limited to non-genetic methods. The advent of environmental DNA (eDNA) technology enables simultaneous examination of both non-genetic and genetic aspects of fish diversity. In this study, we evaluated the ability of eDNA to capture multidimensional fish diversity in the northern South China Sea, with emphasis on phylogenetic diversity. The effect of environmental change and geographical location on multidimensional fish diversity across different seasons was also investigated. The analysis of species accumulation curves revealed that the observed species richness approached an asymptote, achieving 94.7% and 89.5% of the predicted values during the summer and winter, respectively. Alpha diversity of taxonomic (species, 225 vs. species, 102), functional (FRic, 0.51 vs. FRic, 0.19), and phylogenetic (PD, 26.27 vs. PD, 15.81) dimensions were found to be higher in summer compared to winter, with environmental factors significantly influencing these diversities across seasons. Regarding the three dimensions of beta diversity, replacement made a greater relative contribution to total taxonomic, functional, and phylogenetic beta diversity than richness difference. These effects were primarily influenced by water environment factors (e.g., NO2−, SiO32−, surface temperature) during the summer and geographical factors (e.g., longitude and latitude) during the winter. This study provides evidence supporting the feasibility of utilizing eDNA techniques to uncover fish diversity in multiple dimensions, with a specific emphasis on its intrinsic genetic characteristics, which hold substantial value for the protection of diversity and the scientific administration of fishery resources.